1989
DOI: 10.1007/bf00230237
|View full text |Cite
|
Sign up to set email alerts
|

Actions of excitatory amino acid antagonists on synaptic potentials of layer II/III neurons of the cat's visual cortex

Abstract: Actions of excitatory amino acid (EAA) antagonists on the responses of cells in layers II/III and IV of the cat's visual cortex to stimulation of layer VI and the underlying white matter were studied in slice preparations. Antagonists used were 2-amino-5-phosphonovalerate (APV), a selective antagonist for the N-methyl-D-aspartate (NMDA) type of EAA receptors, and kynurenate, a broad-spectrum antagonist for the three types of EAA receptors. In extracellular recordings it was demonstrated that most of the layer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
24
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(31 citation statements)
references
References 47 publications
7
24
0
Order By: Relevance
“…We found that even when we excluded the synaptic delay, the CV WM-IV for ϾP30 (0.31 Ϯ 0.06 m͞s, n ϭ 9) was still Ϸ10-fold smaller than the CV VB-WM (3.28 Ϯ 0.11 m͞s). The calculated synaptic delay for nine cells was 0.61 Ϯ 0.11 ms, which is comparable with the previously reported values for thalamocortical synapses (27)(28)(29).…”
Section: Resultssupporting
confidence: 89%
“…We found that even when we excluded the synaptic delay, the CV WM-IV for ϾP30 (0.31 Ϯ 0.06 m͞s, n ϭ 9) was still Ϸ10-fold smaller than the CV VB-WM (3.28 Ϯ 0.11 m͞s). The calculated synaptic delay for nine cells was 0.61 Ϯ 0.11 ms, which is comparable with the previously reported values for thalamocortical synapses (27)(28)(29).…”
Section: Resultssupporting
confidence: 89%
“…The possibility that inhibition regulates NMDA-mediated activity is consistent with other lines of evidence in area 17 (Artola and Singer, 1987;Shirokawa et al, 1989;Schroeder et al, 1997). The relationship between GABAergic inhibition and NMDA function is probably related to the voltage dependence of NMDA receptors; the binding of extracellular Mg 2ϩ to the channel pore is highly dependent on membrane potential, and changes in the latter could significantly modulate NMDA receptor-mediated activity (for review, see Dingledine, 1999).…”
Section: Direction Selectivity In Supragranular Layers Of Cortexsupporting
confidence: 79%
“…A fundamental difference between layers 2/3 and 4 is the presence in supragranular layers of NMDA receptors, where they have been shown to participate in transmission in vivo (Fox et al, 1989(Fox et al, , 1990 and in vitro (Shirokawa et al, 1989). Our data indicate that AMPA and NMDA receptors both contribute to direction selectivity in supragranular layers (Fig.…”
Section: Direction Selectivity In Supragranular Layers Of Cortexmentioning
confidence: 61%
See 1 more Smart Citation
“…Similarly, the intense immunostained puncta in layer IVC forms a pattern of alternating intensely stained stripes and poorly stained stripes that can be related to geniculocortical afferent terminations (Hubel and Wiesel, 1972;Hendrickson et al, 1978;DeFelipe and Jones, 1991), clusters of dendrites (Peters and Sethares, 1991), and glutamate immunoreactive processes (Carder and Hendry, 1994). This hypothesis is also supported by a large body of literature indicating that excitatory neurotransmission at thalamocortical synapses is primarily mediated by AMPA receptors (Hagihara et al, 1988;Shirokawa et al, 1989;Fox et al, 1989Fox et al, , 1992Nishigori et al, 1990;Gil and Amitai, 1996). Despite the fact that geniculocortical afferent terminals may represent less than 20% of the asymmetrical synapses in layer IVC (Garey and Powell, 1971;Tigges and Tigges, 1979;Peters et al, 1994), physiological evidence indicates that thalamic input plays an essential role in driving cortical cells (Tanaka, 1983;Ferster et al, 1996).…”
Section: Ampa Subunit Organization In Macaque V1mentioning
confidence: 64%